SARS-CoV-2 Drive/Walk-Thru screening centers in Colombia: The CoVIDA project - Andrea Ramirez-Varela (Asociación Colombiana de Infectología, 2021)
Objective: The CoVIDA project is a public-private collaboration led by Universidad de los Andes that contributed to the SARS-CoV-2 epidemiological surveillance in Bogotá and nearby municipalities. We aimed to describe the development and performance of the Drive/Walk-through free RT- PCR for SARS-CoV-2 testing strategy implemented by CoVIDA. Material and method: We performed a descriptive analysis of the characteristics and performance of the CoVIDA Drive/Walk-through testing centers. The model and the process indicators to assess the model's performance were based on international experiences and scientific literature. Two screening centers were imple-mented in shopping centers in the north and south of Bogotá. We reported the number of tests taken, the number of positive tests, and the number of participants that used the model by the type of occupations.Results: In total,36,689 nasopharyngeal RT-PCR tests for SARS-CoV-2 were performed with a 5.75% cumulative positivity. Process indicators showed an excellent performance and an important contribution in reducing barriers to access to testing. Conclusions: the CoVIDA Drive/Walk-through testing centers supported the epidemiological surveillance in asymptomatic or mild-symptomatic population in Bogotá. Low and middle-income countries can use this model as a cost-effective and innovative solution strategy to intensify testing and help mitigate the pandemic.